2024
DOI: 10.1002/fsn3.4047
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antimicrobial activity of the essential oils in different populations of Coriandrum sativum L. (coriander) from Iran and Iraq

Seyed Mehdi Talebi,
Abbas Naser,
Mansour Ghorbanpour

Abstract: Coriander (Coriandrum sativum L.) is an annual herb belonging to the Apiaceae family that is grown worldwide. This aromatic herb has been used for its nutritional value and biological properties. In this study, we compared the essential oil composition and antibacterial activity of coriander seeds from nine Iranian and Iraqi populations for the first time. The seed oils were extracted using a Clevenger‐type apparatus, and their chemical composition was determined using GC and GC/MS Agilent apparatuses. The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…The significance of the first two principal component axes was observed, explaining 67% of the total genotype-environment interaction. On the other hand, Talebi et al [67] reported that linalool chemotypes, distinguished by a particular chemical compound, formed four primary clusters based on the composition of essential oil extracted from coriander seeds. Clustering analyses revealed a notable disparity between Iranian and Iraqi coriander populations.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the first two principal component axes was observed, explaining 67% of the total genotype-environment interaction. On the other hand, Talebi et al [67] reported that linalool chemotypes, distinguished by a particular chemical compound, formed four primary clusters based on the composition of essential oil extracted from coriander seeds. Clustering analyses revealed a notable disparity between Iranian and Iraqi coriander populations.…”
Section: Discussionmentioning
confidence: 99%